High-safety aramid fiber coating diaphragm, preparation method thereof and battery cell

By regulating the cross-sectional pore size of the aramid coating and dispersion of inorganic particles, the lithium-ionization problem caused by narrow and long pores in the prior art is solved, the high temperature resistance and cycling performance of the battery cell are improved, and the high safety and long life of the battery cell are ensured.

CN119133775APending Publication Date: 2024-12-13SINOMA LITHIUM BATTERY SEPARATOR CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411256206.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing aramid-coated diaphragm has long and narrow hole defects in the microstructure of the coating cross-section, which affects the liquid injection distribution of the battery cell, leads to uneven lithium ion concentration, and causes lithium extraction problems, which in turn affects the battery cell capacity and cycling performance, and there are pricks. The risk of penetrating the diaphragm may cause thermal runaway and spontaneous combustion of the power cell.

Method used

By controlling the size and consistency of the cross-sectional pore size of the aramid coating, the ratio and dispersion degree of inorganic particles to aramid are regulated, and high-speed dispersion and high-pressure homogenizer technology are used to ensure uniform dispersion of ceramics, reduce the generation of narrow and long holes, and form a more complete Aramid network structure.

Benefits of technology

It significantly improves the lithium-ion problem of the battery cell, improves high temperature resistance and cycle stability, ensures that the battery cell capacity retention rate is above 85%, reduces the risk of micro-short circuits, and extends the service life of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133775A_ABST
    Figure CN119133775A_ABST
Patent Text Reader

Abstract

The invention provides a high-safety aramid fiber coated diaphragm, a preparation method thereof and a battery cell, and relates to the technical field of battery diaphragms.The high-safety aramid fiber coated diaphragm comprises a base material layer and a heat-resistant layer, the heat-resistant layer comprises a porous structure coating at least formed by aramid fibers and inorganic particles, and the porous structure coating is formed by the base material layer and the inorganic particles. Any cross section, parallel to the thickness direction, of the heat-resistant layer is uniform in hole size and distribution and free of long and narrow holes, the separated aramid fiber network structure is relatively complete, and the diaphragm is good in air permeability, excellent in high-temperature resistance and high in safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery separators, and in particular to a high-safety aramid coated separator and a preparation method thereof and a battery core. Background Art

[0002] Aramid has excellent thermal stability and is usually used as a coating material to improve the heat resistance of the diaphragm to ensure that the coating film does not break when the battery cell is in thermal runaway, thereby delaying or avoiding spontaneous combustion of the battery cell due to thermal runaway. However, the existing aramid coated diaphragm technology pays little attention to the relationship between the pore size of the coating cross section, pore distribution, aramid fiber diameter, aramid network structural integrity, ceramic dispersion and other factors and the thermal runaway and capacity attenuation of the battery cell. In particular, when narrow and long hole defects appear in the microstructure of the coating cross section, it will directly affect the distribution of the electrolyte in the coating after the battery cell is injected, resulting in uneven distribution of lithium ion concentration and lithium precipitation problems in the battery cell. On the one hand, lithium deposition will cause irreversible loss of lithium ions, directly leading to cell capacity decay and affecting cell cycle performance; on the other hand, lithium deposition is easily accompanied by the generation of lithium dendrites, which poses a risk of piercing the diaphragm, followed by a micro-short circuit in the cell and heat generation, which increases the cell temperature and induces the electrolyte side reaction to intensify until it dries up, which also leads to cell capacity decay; in addition, severe micro-short circuits may also cause thermal runaway or even spontaneous combustion of the cell. Therefore, the cross-sectional pore size and consistency control of the aramid-coated diaphragm coating, the diameter of the aramid fiber, and the degree of ceramic dispersion are particularly important for the high safety and high cycle performance requirements of the cell. Summary of the invention

[0003] One of the purposes of the present invention is to provide a high-safety aramid coated diaphragm, which regulates the pore size and consistency of the coating cross section to reduce the narrow and long pore defects in the cross section, significantly improve the lithium deposition problem of the battery cell, and the diameter of the precipitated aramid fibers will be relatively uniform and the network structure will be relatively complete, while taking into account high temperature resistance.

[0004] The second object of the present invention is to provide a method for preparing the high-safety aramid coated diaphragm.

[0005] The third object of the present invention is to provide a battery cell comprising the high-safety aramid coated diaphragm.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] The first aspect of the present invention provides a high-safety aramid coated diaphragm, such as Fig.10 As shown, it includes a substrate layer and a heat-resistant layer, wherein the heat-resistant layer covers one side or both sides of the substrate layer, and the heat-resistant layer comprises a porous structure coating formed by at least aramid and inorganic particles, and any cross section of the heat-resistant layer parallel to the thickness direction has the following characteristics:

[0008] 1) The area S distribution of the cross-sectional hole satisfies: (S90-S10) / S50<1.8, where S50 represents the area corresponding to when the cumulative S distribution percentage reaches 50%, S90 represents the area corresponding to when the cumulative S distribution percentage reaches 90%, and S10 represents the area corresponding to when the cumulative S distribution percentage reaches 10%;

[0009] 2) The area of ​​100 holes in the cross section is counted in order of size, and the range R is less than 0.187 μm. 2 , preferably R<0.18μm 2 , standard deviation StdDev<0.0345μm 2 , preferably StdDev<0.034μm 2 ;

[0010] 3) The distribution of the ratio (W / L) of the maximum length (W) of the cross-sectional hole in the thickness direction to the maximum length (L) perpendicular to the thickness direction should satisfy the following requirement: 0.74<(W / L90-W / L10) / W / L50<1.01, preferably 0.75<(W / L90-W / L10) / W / L50<1.00, wherein W / L50 represents the ratio corresponding to when the cumulative W / L distribution percentage reaches 50%, W / L90 represents the ratio corresponding to when the cumulative W / L distribution percentage reaches 90%, and W / L10 represents the ratio corresponding to when the cumulative W / L distribution percentage reaches 10%.

[0011] The following is a detailed description:

[0012] Features 1):

[0013] The area of ​​the cross-sectional hole is S, and (S90-S10) / S50 represents the area distribution of the cross-sectional hole, which can be, for example, 1.3, 1.4, 1.5, 1.6 and 1.7; when (S90-S10) / S50≥1.8, the ceramics in the coating are unevenly distributed, resulting in poor pore-forming effect. The aramid fiber precipitation diameter in the area with less ceramic distribution is relatively large, and this area is more likely to form long and narrow holes. Although the heat resistance is good, the long and narrow holes can easily cause lithium precipitation in the battery cell and thus affect the cycle performance (capacity retention rate). The aramid fiber precipitation diameter in the area with more ceramics is smaller, and the ceramics are densely accumulated in the aramid fiber structure. The cross-sectional hole area is small. Although the current density is uniform, the thinner aramid fibers are not conducive to the heat resistance of the coating film. The coating film ultimately cannot take into account both heat resistance and cycle performance.

[0014] The cross-sectional hole area S can be tested by the following method:

[0015] Use a blade to vertically cut the aramid coated diaphragm to obtain a cross section in the thickness direction, grind the cross section using an ion milling instrument IM4000plus, observe the cross section of the coating membrane under an electron microscope, and use imageJ software for calculation (insert the scanning electron microscope image of the cross-section hole to be measured into the software, draw its trajectory, and then obtain the internal area of ​​the trajectory).

[0016] The definitions of S90, S10, and S50 are similar to the particle sizes D90, D10, and D50. For example, S50 means that pores smaller than its area account for 50%, and pores larger than its area also account for 50%, reflecting the average pore area.

[0017] S90, S10, S50 can be tested using the following methods:

[0018] In the coating cross-section range (e.g., about 18-30 μm 2 The areas of 100 cross-sectional holes are randomly counted and arranged from small to large, S10 is the area of ​​the 10th hole, S50 is the area of ​​the 50th hole, and S90 is the area of ​​the 90th hole.

[0019] Feature 2):

[0020] The range of cross-sectional hole area is R<0.187μm 2 , for example, it can be 0.120 μm 2 、0.140μm 2 and 0.160 μm 2 , that is, the areas of the 100 cross-sectional holes counted in the measurement feature 1) are arranged from small to large, and the numerical difference between the largest area and the smallest area is the extreme value. When R ≥ 0.187 μm 2 When the coating is thinned, the pore area in the cross section is more discrete, and narrow and long holes are very likely to appear, which leads to a low capacity retention rate of the battery cell.

[0021] The standard deviation of the cross-sectional pore area is StdDev < 0.0345 μm 2 , for example, it can be 0.018 μm 2 、0.021μm 2 , 0.024μm 2 , 0.027μm 2 and 0.030μm 2 , that is, based on the area of ​​the 100 cross-sectional holes mentioned in the previous paragraph, first find the difference between each area and the average area, then square these differences, find the average, and finally take the square root. StdDev>0.0345μm 2 When the coating is thicker, the pore dispersion in the cross section is high, and narrow and long holes are very likely to appear.

[0022] Feature 3):

[0023] The maximum length of the cross-sectional hole in the thickness direction is W, and the maximum length perpendicular to the thickness direction is L. The ratio of the two is W / L (similar to the minor axis / major axis ratio). (W / L90-W / L 10) / W / L50 represents the W / L distribution of the cross-sectional hole, which can be 0.85, 0.82 and 0.79, for example. When (W / L90-W / L10) / W / L50≥1.01 or (W / L90-W / L10) / W / L50≤0.74, the ceramic in the coating is unevenly distributed, resulting in the precipitation of aramid fibers in areas with less ceramic distribution, and the ceramic is not fully filled in the pores between the fibers, which makes it easier to form narrow and long holes.

[0024] The W / L ratio of a cross-sectional hole can be tested using the following method:

[0025] Use a blade to vertically cut the aramid coated diaphragm to obtain a cross-section in the thickness direction. Use an ion milling instrument IM4000plus to grind the cross-section, and observe the coating cross-section under an electron microscope. Use imageJ software to measure the maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of the coating cross-section hole, and calculate the W / L ratio.

[0026] The definitions of W / L90, W / L10 and W / L50 are similar to the particle sizes D90, D10 and D50, respectively. For example, W / L50 means that pores with W / L smaller than it account for 50%, and pores with W / L larger than it also account for 50%, reflecting the W / L of the average pores.

[0027] W / L90, W / L10 and W / L50 can be tested by the following methods:

[0028] In the coating cross-section range (e.g., about 18-30 μm 2 The W / L ratios of 100 cross-sectional holes are randomly counted and arranged from small to large. W / L10 is the W / L ratio of the 10th hole, W / L50 is the W / L ratio of the 50th hole, and W / L90 is the W / L ratio of the 90th hole.

[0029] The heat resistance and cycle stability of the battery cell can be taken into account:

[0030] Furthermore, the thermal shrinkage of the aramid coated membrane in the machine direction MD and the transverse direction TD after being kept at 130°C for 1 hour is less than 1.8%; preferably, the thermal shrinkage of the aramid coated membrane in the machine direction MD after being kept at 130°C for 1 hour is less than 1.8%, and the thermal shrinkage of the transverse direction TD is less than 1.5%.

[0031] Furthermore, the hot needle puncture hole area of ​​the aramid coated diaphragm is less than 0.35mm 2 .

[0032] The battery cell has no capacity attenuation due to lithium deposition, and the battery cell capacity retention rate is good:

[0033] Furthermore, the capacity retention rate of the battery cell composed of the aramid coated separator, the lithium iron phosphate positive electrode and the graphite negative electrode is above 85% after 300 charge and discharge cycles at a 1C rate.

[0034] The aramid coated diaphragm is assembled with a lithium ion secondary battery (graphite as the negative electrode and lithium iron phosphate as the positive electrode) and left to stand at room temperature (25°C) for 24 hours. The charge and discharge cycle is carried out in the voltage range of 2.5V-3.65V at a charge and discharge rate of 1C, and the initial capacity C0 is measured. The capacity after the 300th cycle is measured as C1, and the capacity retention rate (%) = C1 / C0×100%. The higher the capacity retention rate value, the less the discharge capacity decreases and the longer the cycle life. The capacity retention rate of the battery cell assembled using the aramid coated diaphragm is above 85%.

[0035] Further, the heat-resistant layer of the aramid coated diaphragm has an increased air permeability per unit thickness of 20-30 s / 100 cc / μm, for example, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 and 30 s / 100 cc / μm.

[0036] The air permeability increase per unit thickness of the heat-resistant layer = (air permeability of the aramid coated diaphragm - air permeability of the substrate layer) / thickness of the heat-resistant layer.

[0037] Furthermore, the heat-resistant layer of the aramid coated diaphragm has a unit thickness weight of 0.6-1.3 g / m 2 / μm, such as 0.6, 0.8, 0.10 and 0.12 g / m 2 / μm.

[0038] The weight per unit thickness of the heat-resistant layer = (weight of the aramid-coated separator - weight of the substrate layer) / thickness of the heat-resistant layer.

[0039] The substrate layer can be any substrate layer suitable for lithium batteries known in the prior art, for example, it can be a microporous membrane, a porous membrane or a non-woven membrane, a single substrate layer, or a composite substrate layer, such as a polyethylene microporous membrane, a polypropylene microporous membrane, a polyethylene / polypropylene / polyethylene three-layer composite microporous membrane, a polyvinylidene fluoride microporous membrane, a polyimide microporous membrane, a non-woven fabric, etc., but not limited thereto. The source of the substrate layer is not limited, and it can be obtained commercially or prepared by itself according to existing methods. For example, the polyolefin substrate layer can be prepared by unidirectional or bidirectional stretching using a wet or dry process, or prepared by a thermally induced phase separation method.

[0040] There is no particular limitation on the thickness of the substrate layer. Generally, the thickness is less than 20 μm, for example, 4-20 μm, such as 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 and 20 μm.

[0041] There is no particular limitation on the porosity of the substrate layer as long as it is suitable for use as a separator for a lithium battery. For example, the porosity can be 40-55%, such as 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54% and 55%.

[0042] There is no particular limitation on the air permeability of the substrate layer as long as it is suitable for use as a separator for a lithium battery, for example, the air permeability may be 50-300 s / 100 cc, such as 50, 60, 80, 100, 150, 200 and 300 s / 100 cc.

[0043] The main components of the heat-resistant layer are aramid (polyamide fiber) and inorganic particles.

[0044] The aramid is selected from at least one of poly(m-phenylene isophthalamide) (aramid 1313, aramid I) and poly(p-phenylene terephthalamide) (aramid 1414, aramid II), preferably poly(p-phenylene terephthalamide).

[0045] There is no particular limitation on the inorganic particles. In one embodiment, the inorganic particles are ceramic materials and can be selected from one or more of Al2O3, SiO2, TiO2, ZrO2, BaTiO3, BaSO4, MgO, CaO, AlOOH and SiC.

[0046] There is no particular limitation on the thickness of the heat-resistant layer as long as it is suitable for use as a separator for a lithium battery, and for example, it may be 0.5-5 μm, such as 1, 2, 3 and 4 μm.

[0047] The aramid coated separator of the present invention may be manufactured according to the following method, but the present invention is not limited thereto.

[0048] The second aspect of the present invention provides a method for preparing the above-mentioned high-safety aramid coated diaphragm, comprising the following steps:

[0049] (1) mixing an aramid stock solution, inorganic particles and an optional (optional) organic solvent, and dispersing the mixture in a high-speed disperser and a high-pressure homogenizer to obtain an aramid coating slurry;

[0050] The mass ratio of aramid to inorganic particles is (1-2):3;

[0051] The high-speed dispersion speed is 3000-10000rpm, and the high-speed dispersion time is 1-2h;

[0052] The pressure P of the high-pressure homogenizer, the specific surface area S of the inorganic particles, the median particle size D50 of the inorganic particles and the rotational viscosity V of the aramid coating slurry satisfy the following conditions: S×V×(3.58×P+11310) / (1000×D50)>5×10 7 , where: S is 20-50m 2 / g, V is 3000-13000mPa·s, P is 500-1000bar, and D50 is 0.05-0.15μm;

[0053] (2) The aramid coating slurry is coated on at least one side of the substrate layer, and then subjected to a steam bath, water washing, and drying to obtain an aramid coating diaphragm.

[0054] Step (1):

[0055] The aramid stock solution comprises aramid (poly(m-phenylene isophthalamide) or poly(p-phenylene terephthalamide), a cosolvent and an organic solvent, wherein the cosolvent is one or more of CaCl2, KOH, LiCl or pyridine, and the organic solvent is any one of N-methylpyrrolidone (NMP) and dimethylacetamide (DMAc). The aramid solid content in the aramid stock solution is 2±0.2%, and the cosolvent content is ≤10%. The solid content of the aramid coating slurry (total mass of aramid and inorganic particles / total mass of inorganic particles, aramid stock solution and optional organic solvent) is 4-8%.

[0056] Preferably, the aramid in the aramid stock solution is poly(p-phenylene terephthalamide) (para-aramid).

[0057] The inventors have found that the use of para-aramid is more likely to produce narrow elongated holes. To address this problem, the present invention improves the preparation method and can significantly avoid the generation of narrow elongated holes by combining the following specific process factors and conditions:

[0058] By controlling the ratio of inorganic particles to aramid fiber 3:(1-2), under the condition of uniform ceramic dispersion, the higher the proportion of ceramic, the more uniform the pores in the coating, and the lower the probability of narrow and long holes in the coating cross section.

[0059] By controlling the high-speed dispersion speed and time, speed: 3000-10000rpm, time: 1-2h, and high-pressure homogenization pressure, the dispersion degree of ceramics in the slurry is regulated. The better the ceramic dispersion degree, the more uniform the coating pores, the more uniform the aramid fiber diameter, and the fewer narrow and long holes in the coating cross section.

[0060] Inorganic particles BET meets: 20m 2 / g≤BET≤50m 2 / g, preferably 25, 35 and 45m2 / g, etc., to ensure that the inorganic particles in the cross section only occupy a small area. When the total ceramic dispersion of the slurry is better, the larger the BET, the smaller the diameter of the aramid fiber precipitation in the coating, the lower the heat resistance, and the smaller the probability of the occurrence of slits and long holes. The smaller the BET, the larger the diameter of the aramid fiber precipitation in the coating, and the heat resistance is improved. Since the number of inorganic particles is small at this time, they cannot fill the pores between the aramid fibers, and slits and long holes are easier to form, lithium precipitation occurs in the battery cell, the active lithium decreases, and the capacity retention rate decreases. When BET<20m 2 / g, because the ceramic particles are relatively large in size but relatively small in number, the ceramic filling in the coating is insufficient, and the aramid precipitation diameter in the unfilled area is large, which is very easy to form narrow and long holes. 2 / g, the specific surface area is larger, and the corresponding particle size is smaller. The intermolecular van der Waals force has a more significant effect on particle agglomeration, which intensifies the soft agglomeration of ceramic particles and causes the soft agglomerated ceramic particles to be concentrated in a certain area of ​​the coating cross section. The aramid fibers precipitated in this area have a smaller diameter. In other areas where soft agglomerated ceramic particles are not distributed, the pores between the aramid fibers cannot be fully filled due to the small ceramic particle size, which can easily cause the large pores in this area to increase and form narrow and long holes.

[0061] By adjusting the relationship between the pressure of the high-pressure homogenizer (P), the specific surface area of ​​the inorganic particles (S), the median particle size of the inorganic particles (D50) and the rotational viscosity (V) of the aramid coating slurry, when S×V×(3.58×P+1 1310) / (1000×DS0)≤5×10 7 When S×V×(3.58×P+11310) / (1000×D50)>5×10 7 When , the aramid fiber precipitation and ceramic distribution in the coating cross section are relatively uniform, the ceramics are effectively filled in the pores between the fibers, and there are fewer narrow and long holes.

[0062] Ultimately, the pore size, pore distribution, aramid fiber diameter, aramid network structural integrity and ceramic dispersion of the coating cross section are adjusted to obtain the characteristic product.

[0063] Step (2):

[0064] The coating method is not particularly limited as long as it is suitable for preparing the separator, for example, wire bar coating, micro gravure roll coating, doctor blade coating, slot extrusion coating, and the like.

[0065] There are no particular restrictions on the steam bath, and it can be performed at ordinary temperature and humidity.

[0066] There is no special limitation on the water washing method. Generally, 2-8 levels of water tanks are set, all of which are pure water settings. The pure water in the water tank adopts an overflow method from back to front. Each water tank outlet needs to be equipped with an air knife or pressure roller to reduce the diaphragm from carrying water from the previous water tank into the next water tank.

[0067] There is no particular limitation on the drying method as long as it is suitable for preparing the separator. For example, drying may be used, preferably at 60-90°C.

[0068] According to a third aspect of the present invention, there is provided a battery cell comprising the above-mentioned aramid coated separator.

[0069] Aramid coated diaphragms can be used in different types of battery cells and can be selected according to actual needs. For example, they can be used in secondary batteries such as lithium-ion batteries and sodium-ion batteries.

[0070] Beneficial effects:

[0071] 1. The present invention avoids the problem of lithium precipitation caused by uneven distribution of lithium ion concentration in the coating due to the presence of narrow and long holes by limiting the cross-sectional pore area distribution, the degree of discreteness of the cross-sectional pore area, the W / L distribution of the cross-sectional pores, the specific surface area of ​​the inorganic particles, etc., while the obtained aramid coated diaphragm has high temperature resistance.

[0072] 2. The present invention prepares the aramid coated diaphragm by adjusting the ratio of inorganic particles to aramid, the specific surface area of ​​the inorganic particles, the high-speed dispersion speed and time, and the relationship between P, S, V and D50 to achieve the purpose of controlling the pore size of the coating cross section, pore distribution, aramid fiber diameter size, aramid network structure integrity and ceramic dispersibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is an electron microscope image of the diaphragm prepared in Comparative Example 1;

[0074] Figure 2 This is an electron microscope image of the diaphragm prepared in Comparative Example 2;

[0075] Figure 3 This is an electron microscope image of the diaphragm prepared in Comparative Example 3;

[0076] Figure 4 This is an electron microscope image of the diaphragm prepared in Comparative Example 4;

[0077] Figure 5 This is an electron microscope image of the diaphragm prepared in Comparative Example 5;

[0078] Figure 6 This is an electron microscope image of the diaphragm prepared in Comparative Example 6;

[0079] Figure 7 This is an electron microscope image of the diaphragm prepared in Example 1;

[0080] Figure 8 This is an electron microscope image of the diaphragm prepared in Example 2;

[0081] Fig. 9 This is an electron microscope image of the diaphragm prepared in Example 3;

[0082] Fig.10 It is a schematic diagram of the structure of the aramid coated diaphragm of the present invention;

[0083] Illustration: 1-base material layer, 2-heat-resistant layer. DETAILED DESCRIPTION

[0084] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0085] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0086] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0087] Example 1

[0088] Add 2.4 g of a specific surface area of ​​about 45 m 2 / g Al2O3 ceramic and 60g para-aramid stock solution (rotational viscosity of 3000mPa·s, solid content of 2%) were dispersed at high speed at 8000rpm for 1h, ice bath was used during high-speed dispersion, and then dispersed once by high-pressure homogenizer at 500bar pressure. During the homogenization and dispersion process, condensed water was circulated to cool down, and a slurry with a solid content of about 5.77% was obtained. A 9μm base film (manufactured by Zhongcai Lithium Membrane Co., Ltd.) was coated with a wire rod to obtain a coated wet film, and then a coating dry film with a coating thickness of about 3μm was obtained through a steam bath (65℃, humidity RH80%), water washing, and drying (60℃, 30min) process, and the air permeability, gram weight, and heat resistance of the coated diaphragm were tested. The raw materials and preparation parameters are shown in Table 1.

[0089] Use the IM4000plus ion milling instrument to prepare cross-section samples of the coated film: fold the aluminum foil in half, and then clamp the cut diaphragm sample in the aluminum foil close to the fold line of the aluminum foil. At this time, make the diaphragm about 3mm shorter than the aluminum foil at one end, apply a proper amount of glue on this blank space, and then quickly close the aluminum foil. Cut off the excess aluminum foil with a blade, and then glue the sample to the silicon plate. Use a blade to cut the diaphragm vertically along the edge of the silicon plate to obtain the cross section of the sample to be processed. Paste the above cross-section sample on a special sample stage, and the silicon plate protrudes from the edge of the sample stage by about 2mm. Install the special sample stage on the cross-section processing sample holder, press the sample stage fixing screw with a hexagonal rod to slide it next to the MASK, and place the sample close to the MASK, and then tighten the fixing screw. Turn on the ion milling instrument for grinding.

[0090] The cross-sectional pore structure of the coating was observed under an electron microscope. Figure 7 The cross-sectional features are as follows:

[0091] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.063 μm 2 , S10=0.016μm 2 , S50=0.027μm 2 , (S90-S10) / S50=1.74; range R=0.123μm 2 , standard deviation StdDev=0.0217μm 2 .

[0092] The maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes were measured, and the W / L ratio was calculated. After arranging them from small to large, the following values ​​were obtained: W / L90=1.368, W / L10=0.639, W / L50=0.889, (W / L90-W / L10) / W / L50=0.821.

[0093] Example 2

[0094] 40 g of para-aramid stock solution (rotational viscosity of 3000 mPa·s, solid content of 2%) was used to prepare the slurry, the pressure of the high-pressure homogenizer was 800 bar, and other operations were the same as in Example 1. The raw materials and preparation parameters are shown in Table 1.

[0095] The sample was prepared in the same manner as in Example 1, and the cross-sectional pore structure of the coating was observed under an electron microscope. Figure 8 As shown, the cross-sectional features are as follows:

[0096] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.048 μm 2 , S10=0.019μm 2 , S50=0.028μm 2, (S90-S10) / S50=1.036; range R=0.100μm 2 , standard deviation StdDev=0.0163μm 2 .

[0097] Measure the maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes, calculate the W / L ratio, and arrange them from small to large to obtain: W / L90=1.000, W / L10=0.423, W / L50=0.625, (W / L90-W / L10) / W / L50=0.923.

[0098] Example 3

[0099] 80 g of para-aramid stock solution (rotational viscosity of 3000 mPa·s, solid content of 2%) was used to prepare the slurry, and other operations were the same as those in Example 1. The raw materials and preparation parameters are shown in Table 1.

[0100] The sample was prepared in the same manner as in Example 1, and the cross-sectional pore structure of the coating was observed under an electron microscope. Fig. 9 As shown, the cross-sectional features are as follows:

[0101] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.048 μm 2 , S10=0.015μm 2 , S50=0.025μm 2 , (S90-S10) / S50=1.320; range R=0.062μm 2 , standard deviation StdDev=0.015μm 2 .

[0102] The maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes were measured, and the W / L ratio was calculated. After arranging them from small to large, the following results were obtained: W / L90=1.308, W / L10=0.600, W / L50=0.889, (W / L90-W / L10) / W / L50=0.821.

[0103] Comparative Example 1

[0104] Add 4g NMP, 2.4g of 2 / g Al203 ceramic and 80g para-aramid stock solution (rotational viscosity of 3000mPa·s, solid content of 2%) were dispersed at a high speed of 4000rpm for 1h, and an ice bath was used during the high-speed dispersion process to obtain a slurry with a solid content of about 4.63%. A 9μm base film was coated with a wire rod to obtain a coated wet film, and then a coating dry film with a coating thickness of about 3μm was obtained through a steam bath (65℃, humidity RH80%), water washing, and drying (60℃, 30min) process, and the air permeability, gram weight, and heat resistance of the coated diaphragm were tested. The raw materials and preparation parameters are shown in Table 1.

[0105] The sample was prepared in the same manner as in Example 1, and the cross-sectional pore structure of the coating was observed under an electron microscope. Figure 1 As shown, the cross-sectional features are as follows:

[0106] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.093 μm 2 , S10=0.006μm 2 , S50=0.023μm 2 , (S90-S10) / S50=3.783; range R=0.903μm 2 , standard deviation StdDev=0.0935μm 2 .

[0107] The maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes were measured, and the W / L ratio was calculated. After arranging them from small to large, the following values ​​were obtained: W / L90=1.126, W / L10=0.380, W / L50=0.668, (W / L90-W / L10) / W / L50=1.117.

[0108] Comparative Example 2

[0109] Add 4g NMP, 2.4g of 2 / g of A1203 ceramic and 80g of para-aramid stock solution (rotational viscosity of 3000mPa·s, solid content of 2%) were dispersed at a high speed of 6000rpm for 1h, and an ice bath was used during the high-speed dispersion process to obtain a slurry with a solid content of about 4.63%. A 9μrm base film was coated with a wire rod to obtain a coated wet film, and then a coating dry film with a coating thickness of about 3μm was obtained through a steam bath (65℃, humidity RH80%), water washing, and drying (60℃, 30min) process, and the air permeability, gram weight, and heat resistance of the coated diaphragm were tested. The raw materials and preparation parameters are shown in Table 1.

[0110] The sample was prepared in the manner of Example 1, and the cross-sectional pore structure characteristics of the coating under electron microscopy were as follows: Figure 2 As shown:

[0111] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.076 μm 2 , S10=0.006μm 2 , S50=0.023μm 2 , (S90-S10) / S50=3.043; range R=0.232μm 2 , standard deviation StdDev=0.0396μm 2 .

[0112] The maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes were measured, and the W / L ratio was calculated. After arranging them from small to large, the following values ​​were obtained: W / L90=1.227, W / L10=0.376, W / L50=0.667, (W / L90-W / L10) / W / L50=1.276.

[0113] Comparative Example 3

[0114] Add 4g NMP, 2.4g of 2 / g Al203 ceramic and 80g para-aramid stock solution (rotational viscosity of 3000mPa·s, solid content of 2%) were dispersed at a high speed of 6000rpm for 1h, and an ice bath was used during the high-speed dispersion process to obtain a slurry with a solid content of about 4.63%. A 9μm base film was coated with a wire rod to obtain a coated wet film, and then a coating dry film with a coating thickness of about 3μm was obtained through a steam bath (65℃, humidity RH80%), water washing, and drying (60℃, 30min) process, and the air permeability, gram weight, and heat resistance of the coated diaphragm were tested. The raw materials and preparation parameters are shown in Table 1.

[0115] The sample was prepared in the manner of Example 1, and the cross-sectional pore structure characteristics of the coating under electron microscopy were as follows: Figure 3 As shown:

[0116] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.084 μm 2 , S10=0.008μm 2 , S50=0.025μm 2 , (S90-S10) / S50=3.040; range R=0.19μm 2 , standard deviation StdDev=0.035μm 2 .

[0117] The maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes were measured, and the W / L ratio was calculated. After arranging them from small to large, the following values ​​were obtained: W / L90=1.285, W / L10=0.428, W / L50=0.709, (W / L90-W / L10) / W / L50=1.210.

[0118] Comparative Example 4

[0119] Add 4g NMP, 2.4g of 2 / g of A1203 ceramic and 60g of para-aramid stock solution (rotational viscosity of 3000mPa·s, solid content of 2%) were dispersed at high speed at 8000rpm for 1h, ice bath during high-speed dispersion, and then dispersed once by high-pressure homogenizer at 100bar pressure. During the homogenization and dispersion process, condensed water was circulated to cool down to obtain a slurry with a solid content of about 5.77%. A 9μm base film was coated with a wire rod to obtain a coated wet film, and then a coating dry film with a coating thickness of about 3μm was obtained through a steam bath (65℃, humidity RH80%), water washing, and drying (60℃, 30min) process, and the air permeability, gram weight, and heat resistance of the coated diaphragm were tested. The raw materials and preparation parameters are shown in Table 1.

[0120] The sample was prepared in the manner of Example 1, and the cross-sectional pore structure characteristics of the coating under electron microscopy were as follows: Figure 4 As shown:

[0121] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.089 μm 2 , S10=0.015μm 2 , S50=0.028μm 2 , (S90-S10) / S50=2.643; range R=0.255μm 2 , standard deviation StdDev=0.0391μm 2 .

[0122] The maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes were measured, and the W / L ratio was calculated. After arranging them from small to large, the following values ​​were obtained: W / L90=1.202, W / L10=0.415, W / L50=0.677, (W / L90-W / L10) / W / L50=1.164.

[0123] Comparative Example 5

[0124] Add 4g NMP, 2.4g of 2 / g of A1203 ceramic and 80g of para-aramid stock solution (rotational viscosity of 3000mPa·s, solid content of 2%) were dispersed at high speed at 8000rpm for 1h, ice bath during high-speed dispersion, and then dispersed once by high-pressure homogenizer at 300bar pressure. During the homogenization and dispersion process, condensed water was circulated to cool down, and a slurry with a solid content of about 4.63% was obtained. A 9μm base film was coated with a wire rod to obtain a coated wet film, and then a coating dry film with a coating thickness of about 3μm was obtained through a steam bath (65℃, humidity RH80%), water washing, and drying (60℃, 30min) process, and the air permeability, gram weight, and heat resistance of the coated diaphragm were tested. The raw materials and preparation parameters are shown in Table 1.

[0125] The sample was prepared in the manner of Example 1, and the cross-sectional pore structure characteristics of the coating under electron microscopy were as follows: Figure 5 As shown:

[0126] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.126 μm 2 , S10=0.032μm 2 , S50=0.052μm 2 , (S90-S10) / S50=1.808; range R=0.265μm 2 , standard deviation StdDev=0.0532μm 2 .

[0127] The maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes were measured, and the W / L ratio was calculated. After arranging them from small to large, the following values ​​were obtained: W / L90=1.247, W / L10=0.632, W / L50=0.835, (W / L90-W / L10) / W / L50=1.247.

[0128] Comparative Example 6

[0129] Add 4g NMP, 2.4g of 2 / g of A1203 ceramic and 80g of para-aramid stock solution (rotational viscosity of 3000mPa·s, solid content of 2%) were dispersed at high speed at 8000rpm for 1h, ice bath during high-speed dispersion, and then dispersed once by high-pressure homogenizer at 1000bar pressure. During the homogenization and dispersion process, condensed water was circulated to cool down to obtain a slurry with a solid content of about 4.63%. A 9μm base film was coated with a wire rod to obtain a coated wet film, and then a coating dry film with a coating thickness of about 3μm was obtained through a steam bath (65℃, humidity RH80%), water washing, and drying (60℃, 30min), and the air permeability, gram weight, and heat resistance of the coated diaphragm were tested. The raw materials and preparation parameters are shown in Table 1.

[0130] The sample was prepared in the manner of Example 1, and the cross-sectional pore structure characteristics of the coating under electron microscopy were as follows: Figure 6 As shown:

[0131] Take 100 cross-sectional holes, calculate their area S, and arrange them from small to large to get: S90 = 0.105 μm 2 , S10=0.014μm 2 , S50=0.029μm 2 , (S90-S10) / S50=3.138; range R=0.338μm 2 , standard deviation StdDev=0.0536μm 2 .

[0132] The maximum length W in the thickness direction and the maximum length L perpendicular to the thickness direction of each of the 100 holes were measured, and the W / L ratio was calculated. After arranging them from small to large, the following values ​​were obtained: W / L90=1.028, W / L10=0.385, W / L50=0.612, (W / L90-W / L10) / W / L50=1.050.

[0133] The performance tests were performed on the diaphragms prepared in the examples and comparative examples. The specific test methods are as follows:

[0134]

Breathability

[0135] Test according to the method specified in GB / T 1038;

[0136]

Weight

[0137] That is, the surface density is tested according to the method specified in GB / T 36363-2018;

[0138]

Heat shrinkage rate

[0139] The test was carried out in accordance with the requirements of GB / T36363-2018. A 100×100mm sample was taken from the coating film and placed in a blast oven at 130°C for 1 hour. The heat shrinkage rate can be calculated by the following formula:

[0140]

[0141] [Hot needle puncture hole area]

[0142] Heat a soldering iron with a diameter of 0.4 mm to 600°C. After the temperature stabilizes, pierce the diaphragm vertically with the soldering iron and keep it still for 20 seconds. Then move the soldering iron away in the vertical direction and measure the area of ​​the pierced hole with an imager.

[0143]

Battery cell capacity retention rate

[0144] The capacity retention rate of a battery cell measures its ability to retain capacity during the charge and discharge cycle, that is, its ability to resist capacity attenuation. Its value is defined as the ratio of the fully discharged capacity to the initial capacity of the battery cell (the positive electrode is lithium iron phosphate and the negative electrode is graphite) after the 300th cycle, where 100% state of charge (SOC) is when not discharged and 0% SOC after full discharge.

[0145] The results are shown in Table 2.

[0146] Table 1:

[0147]

[0148] Table 2:

[0149]

[0150]

[0151] Result analysis: The coating film provided by the present invention has uniform cross-sectional pore size and no narrow and long holes, the precipitated aramid fiber network structure is relatively complete, meets the specified cross-sectional pore size and structural distribution, has excellent heat resistance, and has a high cell capacity retention rate. However, the coating film that does not conform to the present invention has uneven cross-sectional pore distribution and has more narrow and long holes, has poor heat resistance, and has a low cell capacity retention rate.

[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-safety aramid coated diaphragm, characterized in that: The high-safety aramid coated diaphragm comprises: a substrate layer and a heat-resistant layer, wherein the heat-resistant layer covers one or both sides of the substrate layer, wherein the heat-resistant layer comprises a porous structure coating formed by at least aramid and inorganic particles, and any cross section of the heat-resistant layer parallel to the thickness direction has the following characteristics: 1) The area S distribution of the cross-sectional hole satisfies: (S90-S10) / S50<1.8, where S50 represents the area corresponding to when the cumulative S distribution percentage reaches 50%, S90 represents the area corresponding to when the cumulative S distribution percentage reaches 90%, and S10 represents the area corresponding to when the cumulative S distribution percentage reaches 10%; 2) The area of ​​100 holes in the cross section is counted in order of size, and the range R is less than 0.187 μm. 2 , standard deviation StdDev<0.0345μm 2 ; 3) The ratio W / L distribution of the maximum length W in the thickness direction of the cross-sectional hole to the maximum length L perpendicular to the thickness direction satisfies: 0.74<(W / L90-W / L10) / W / LS0<1.01, where W / L50 represents the ratio corresponding to when the cumulative W / L distribution percentage reaches 50%, W / L90 represents the ratio corresponding to when the cumulative W / L distribution percentage reaches 90%, and W / L10 represents the ratio corresponding to when the cumulative W / L distribution percentage reaches 10%.

2. The aramid coated diaphragm according to claim 1, characterized in that: The heat shrinkage of the aramid coated diaphragm in the machine direction MD and transverse direction TD after being kept at 130°C for 1 hour is less than 1.8%; the hot needle puncture hole area of ​​the aramid coated diaphragm is less than 0.35mm 2 .

3. The aramid coated diaphragm according to claim 1, characterized in that: The battery cell consisting of an aramid coated diaphragm, a lithium iron phosphate positive electrode, and a graphite negative electrode has a capacity retention rate of over 85% after 300 charge and discharge cycles at a 1C rate.

4. The aramid coated diaphragm according to claim 1, characterized in that: The air permeability value per unit thickness of the heat-resistant layer of the aramid coated diaphragm is 20-30s / 100cc / μm.

5. The aramid coated diaphragm according to claim 1, characterized in that: The unit thickness and gram weight of the heat-resistant layer of the aramid coated diaphragm is 0.6-1.3g / m 2 / μm.

6. A method for preparing the high-safety aramid coated diaphragm according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing an aramid stock solution, inorganic particles and an optional organic solvent, and dispersing the mixture in a high-speed disperser and a high-pressure homogenizer to obtain an aramid coating slurry; The mass ratio of aramid to inorganic particles is (1-2):3; The high-speed dispersion speed is 3000-10000rpm, and the high-speed dispersion time is 1-2h; The following conditions are satisfied between the pressure P of the high-pressure homogenizer, the specific surface area S of the inorganic particles, the median particle size D50 of the inorganic particles and the rotational viscosity V of the aramid coating slurry: S×V×(3.58×P+11310) / (1000×D50)>5×10 7 , where: S is 20-50m 2 / g, V is 3000-13000mPa·s, P is 500-1000bar, and D50 is 0.05-0.15μm; (2) The aramid coating slurry is coated on at least one side of the substrate layer, and then subjected to a steam bath, water washing and drying to obtain an aramid coating diaphragm.

7. The preparation method according to claim 6, characterized in that: In the step (1), the aramid is at least one of poly(m-phenylene isophthalamide) and poly(p-phenylene terephthalamide).

8. The preparation method according to claim 6, characterized in that: In the step (1), the organic solvent is any one of N-methylpyrrolidone and dimethylacetamide.

9. A battery cell, characterized in that: The invention comprises the high-safety aramid coated diaphragm as described in any one of claims 1 to 5.

Citation Information

Cited By

  • Diaphragm and preparation method thereof, battery, battery pack and electric equipment

    CN121416765A

  • A diaphragm, a method for manufacturing the same, a battery, a battery pack, and an electric device

    CN121416765B